Composition for enhancing athletic endurance and performance - Mohamed, Suhaila; Mohamad Shalan, Nor Aijratul Asikin; Wan Osman, Wan Nurfarahin (2013)
The present invention discloses a composition for preventing fatigue and enhancing athletic endurance or performance comprising a plant extract from the family Rubiaceae and/or Labiatae. Also disclosed is use of the composition in the manufacture of a preparation that prevents fatigue and enhances athletic endurance or performance.